Wayne Booth, Why Ethical Criticism Fell on Hard Times (ENTHYMEMA, 2010)
In this article, Wayne Booth imagines a dialogue between him and the great English critic of 18th century, Samuel Johnson in which the second shows his indignation about the reticence of contemporary critics in expressing well defended value judgements of literary works. Starting from the Johnson’s fictional remark, Booth develops a reflection about the importance and the validity of value judgements and promotes an ethical criticism of narrative. Bringing out the elements who threw discredit on it in the actual survey and finding them on the «theoretical rejection of inquiry into “values”», in «the conviction that true reason proceeds by means of critical doubt», the «awareness of immense variability», and finally «the triumph of theories of art as abstract form», afterwards, Booth illustrates five peculiarities he thinks to be hoped for ethical criticism: universality, reflexivity, reciprocity, leading into ultimate questions, anti-utilitarianism.